Managing partnerships for payment product distribution How financial technology companies can balance opportunities and risks - Pilhall, Klara (My University, 2023)
Driven partly by the introduction of financial technology (fintech), the global payment industry has undergone a rapid transformation during the past decades toward digital solutions and online payments. Along with this transformation, financial crime and the challenges of efficiently managing associated risks have increased. Despite multiple competitive advantages, fintech companies face challenges related to the changing dynamics in the payment industry and increasingly need to invest in technological innovation to renew their distribution channels and make payments easier, faster, and more accessible while promoting security. At the same time, business ecosystems have increasingly emerged across sectors to address uncertainties and co-evolution, promoting business collaboration for resilience and agility in networks of strategic partnerships. This study aims to explore how fintech companies that provide online financial services can manage risks related to financial crime when partnering with third-party actors in business ecosystems for payment product distribution. A single-case study is performed, relying on qualitative research through semi-structured interviews at the case company and applying a thematic analysis to analyze the obtained data. The study identifies that risks related to financial crime affect fintech companies that provide online financial services in multiple ways when partnering with third-party actors in business ecosystems for payment product distribution. These effects mainly concern the increased third-party dependency on external actors and the related impact on other areas that should be considered. Moreover, the study proposes actionable solutions to manage these risks. First, measures should be implemented for alignment and agreement to promote collaboration and coordination. Second, actions could be taken to incentivize adherence to the agreed risk standards. Third, fintech companies could benefit from complementing these measures with internal mechanisms to monitor and control that partners adhere to agreed risk standards and limit the risk exposure created by their partnerships. Finally, management should be involved in risk decisions and determine a dynamic risk appetite to respond to the changing dynamics in the payment industry along with these partnerships.
Keywords: Business ecosystems; partnerships; interdependence; coordination; collaboration; payment industry; online payments; financial technology; fintech; payment product distribution; financial crime; risk management; risk appetite